ANALISIS HUKUM SISTEM PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIB BATAM - Respationo, H. M. Soerya; Prasetiasari, Christiani; Suwalla, Nicha; Zaiana, Auliya Fitri; Sahputra, Rifaldi Dwi (Penerbit Goodwood, 2025)
Purpose: This study aims to determine the legal regulation and effectiveness of the compensation training system in Batam Class IIB Women's Correctional Institution, with a focus on the social reintegration of drivers as responsible citizens. Methodology: The study uses normative and empirical legal analysis. Normative analysis includes a review of related legal documents, while empirical analysis includes interviews with community officers at the stalls concerned. Results: The findings show that the training system in prisons is in accordance with existing regulations, but its implementation is not optimal. Obstacles include inconsistency in regulatory provisions, time constraints, lack of experienced service, unsustainable systems, and lack of cooperation from drivers. Conclusions: Training at the Batam Class IIB Women's Prison is in accordance with regulations, but it is not optimal due to various obstacles. Improvement efforts are carried out through government support, partnerships with the private sector, as well as focusing on psychological rehabilitation and improving the skills of officers to improve the quality of services for inmates. Limitations: This research is limited to Batam Class IIB Women's Correctional Institution and may not reflect the conditions in other correctional institutions. Contribution: This study provides recommendations for improving regulations and coaching practices, with the hope of increasing the effectiveness of driver social reintegration.